Fungal‐induced glycolysis in macrophages promotes colon cancer by enhancing innate lymphoid cell secretion of IL‐22. (16th February 2021) - Zhu, Yanan; Shi, Tao; Lu, Xia; Xu, Zhen; Qu, Junxing; Zhang, Zhiyong; Shi, Guoping; Shen, Sunan; Hou, Yayi; Chen, Yugen; Wang, Tingting
Abstract: Incorporation of microbiome data has recently become important for prevention, diagnosis, and treatment of colorectal cancer, and several species of bacteria were shown to be associated with carcinogenesis. However, the role of commensal fungi in colon cancer remains poorly understood. Here, we report that mice lacking the c‐type lectin Dectin‐3 ( Dectin‐3 −/− ) show increased tumorigenesis and Candida albicans burden upon chemical induction. Elevated C. albicans load triggered glycolysis in macrophages and interleukin‐7 (IL‐7) secretion. IL‐7 induced IL‐22 production in RORγt + (group 3) innate lymphoid cells (ILC3s) via aryl hydrocarbon receptor and STAT3. Consistently, IL‐22 frequency in tumor tissues of colon cancer patients positively correlated with fungal burden, indicating the relevance of this regulatory axis in human disease. These results establish a C. albicans ‐driven crosstalk between macrophages and innate lymphoid cells in the intestine and expand our understanding on how commensal mycobiota regulate host immunity and promote tumorigenesis. SYNOPSIS: Contribution of gut‐resident mycobiota and their host recognition receptors to colitis‐associated colon cancer (CAC) remains unclear. Here, deficiency in the surface lectin Dectin‐3 is shown to induce fungal dysbiosis and tumorigenesis in mice, skewing immune cell metabolism and cytokine signaling. Depletion of c‐type lectin Dectin‐3 increases Candida albicans burden and CAC in vivo . Elevated C. albicans load triggers glycolysis and inflammatory IL‐7 secretion from macrophages. Macrophage‐derived IL‐7 induces IL‐22 secretion by group‐3 innate lymphoid cells, as well as cancer development. Antifungal treatment ameliorates CAC in Dectin‐3 ‐deficient mice. Abstract : Lack of the Candida albicans recognition receptor Dectin‐3 in mice triggers aberrant immune cell metabolism and tumorigenic cytokine signaling.